The teaching of law post Bologna - Mimoso, Maria João (2018)
The Bologna process aims to harmonize European Higher Education. This implies serious changes and challenges for the Legal Higher education institutions and scholars, as this realm of knowledge should now provide skills for the exercise of a legal profession at a transnational level. Law teaching in most institutions simply tried to cope up with the Europeanization process by introducing pale cosmetic changes and therefore not adapting to the European reality and needs. The main objectives are to summarize Bologna’s objectives applied to the teaching/learning of law, assessing various solutions and cases and trying to deliver a ‘best practice’ draft. After a comprehensive study on the implementation of the Bologna process and its results, we will be able to make a critical judgment on the teaching of law. Matter ‘de iure condendo’ proposes education policies that enable a holistic view of the law.